Social Responsibility and Disposition in Educational Institutions - Guerrero Fernández, Jorge Angel (2024)
The purpose of this study was to examine whether social responsibility is related to dispositional attitudes and whether it is possible to improve and strengthen the knowledge of these variables in education. The methodology was descriptive, correlational, non-experimental and cross-sectional with a quantitative approach. The survey was used as a data collection technique with a Likert scale questionnaire. The study population was 193 people belonging to the community of the Public Educational Institution N°20123, Capilla de Asia, Cañete, with a sample of 130 people including administrative staff, teachers and students from the third year of secondary school onwards. The research was carried out during the year 2022. The results show the perception and the level of knowledge that the population has about social responsibility and the dispositional attitude, which was positive and moderate, so that through sustainable actions in work plans and activities it is possible to strengthen the concepts raised in this research in the participating actors of the educational community studied.